Pedagogical Conditions of Shaping Motor Competence in Physical Education of Students of Special Medical Groups - Корягін, В. М.; Блавт, О. З. (Physical Education Theory and Methodology, 2016)
Study objective. To define the pedagogical conditions of shaping motor competence in students of special medical groups during physical education at higher educational institutions. Study methods: theoretical analysis, systematization, comparison of different views on the issue under study, methodological and special literature collation, general scientific methods of theoretical level: analogy, analysis, synthesis, abstraction, induction. Study results. The study addresses the issues of indicating the pedagogical conditions necessary for the effective shaping of the motor competence in students of special medical groups during their physical education at higher educational institutions. The data analysis and collation of the data collected from the scientific, methodological and special literature helped outline and organize their index, which is a pre-requisite for ensuring the process effectiveness. We recommend using the study results as a major foundation for re-organization of the scientific and methodological aspects of physical education of students with health problems to ensure their motor competence effectively shaped.